ISOLATION AND STRUCTURAL ELUCIDATION OF BIOACTIVE CONSTITUENTS OF COFFEABREVIPES HIERN AND PSEUDOCERATINAPURPUREA CARTER (2014)
The increase in the incidence of Alzheimer disease and infections caused by Mycobacterium tuberculosis are of considerable global health challenge. The inability of existing drugs to cure the Alzheimer disease and the rise in multi-drugs resistant strains of M. tuberculosis has led to continuous search for new anti-alzheimer and antimycobacterial drugs. Terrestrial plants and marine organisms have been major sources of bioactive components for drug development. This study was designed to isolate the chemical constituents, and investigate potential antimycobacterial activity of Coffeabrevipes and antiacetylcholinesterase activity of the marine sponge Pseudoceratinapurpurea based on their ethnomedicinal uses. Dried whole plant of C. brevipes (5.0 kg) was extracted with ethanol. The crude extract was macerated with hexane, chloroform and ethylacetate successively. These fractions were screened against two clinical strains of M. tuberculosis (ZMC 303 and 050) at standard load of 10-2 and 10-4 inoculum concentrations using egg enriched Lowensten Jensen medium following standard method. Isoniazid, dihydrostreptomycin, ethambutol and rifampicin were used as positive controls. Freeze dried P. purpurea (1 kg) was extracted with methanol:tetrachloroethylene (1:1). The obtained extract was successively partitioned with hexane, tetrachloroethylene, chloroform and butanol. The fractions were assayed for acetylcholinesterase inhibition using microplate method with galanthamine as positive control. The bioactive compounds were isolated using chromatographic techniques. Structural elucidations of the isolated compounds were carried out using infrared (IR), ultraviolet, 1D and 2D nuclear magnetic resonance augmented with Mass spectroscopy (MS). The C. brevipes crude extract yielded hexane (7.4 g), chloroform (8.5 g) and ethylacetate (9.3 g) fractions. Similar Minimum Inhibitory Concentration (MIC) against ZMC 303 and 050, were obtained for hexane (5 mg/mL), Chloroform and ethylacetate (>1000 mg/mL) fractions. The MIC of isoniazid, dihydrostreptomycin, and ethambutol were 0.2, 8.0 and 2.0 g/L respectively. Rifampicin was not active against both strains. Two new flavonoids were isolated from C.brevipes named Coffethone A and B with absorptions due to hydroxyl, carbonyl and aromatic C=C groups at ? max 3435, 1712 and 1400-1600 cm-1 in the IR spectrum. The characteristic NMR signals of flavonoids were seen at ? (ppm) of 12.2(1Hs), 12.1(1Hs), 7.8(1Hd, J=7Hz), 7.6(1Hd, J=7Hz), 7.7(1Hs) and 7.1(1Hs). The MS of coffethone A and B suggested the molecular formular C23H24O5 and C23H26O4 at m/z 380.43 and 366.18 respectively. The P. purpurea extract gave hexane (7.4 g), tetrachloroethylene (79.1 g), chloroform (66.4 g) and butanol (115.4 g) fractions. The Acetylcholinesterase inhibitory activity for butanol (93.7%) and chloroform (91.9%) fractions were obtained. Other fractions showed no activities. Three compounds, Bromospiranol, Iso-anomoian and Aplyzansine were isolated from P.purpurea. Their IR spectra showed similar absorption band for the presence of hydroxyl, amide carbonyl and amine at 3400, 1695 and 3300 cm-1. The MS revealed clusters of peaks for pseudomolecular ion at m/z 973.0/974.9/976.9 725/727/730/732 and 740/742/744/746 indicating the presence of bromine atoms in bromospiranol, Iso-anomoian and Aplyzansine respectively. Coffeabrevipes and Pseudoceratinapurpurea extracts are potential sources of antimycobacterial and anti-alzheimer drugs respectively. The new isolated compounds have increased the library of natural products.